Transformasi Data Geospasial: Masjid Dan Mushalla Di Kelurahan Kampung Baru Nan XX - Saputra, David; Astri, Renita; Sularno, Sularno (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
The Kampung Baru Village Mosque/Musalla Geographic Information System (GIS) is a web-based application designed to provide accurate and easily accessible information about the locations, facilities, and activity schedules of mosques and musallas in the area. The system utilizes digital mapping technology to visually and interactively display spatial data. Users can search for mosques or musallas based on name, location, or desired facilities. Additionally, the system is equipped with a navigation feature integrated with popular mapping applications to facilitate users in finding routes to places of worship. With this system, it is hoped that it can improve convenience and ease for Muslims in carrying out their religious duties and strengthen ties among the congregation.